Pemberdayaan Demang Dan Mantir Adat Melalui Pelatihan Penyusunan Surat Kesepakatan Damai di Kecamatan Sebangau Kota Palangka Raya Provinsi Kalimantan Tengah - Joanita Jalianery; Ariani Yestati; Aliya Suci Maghfirli (Pusat Riset dan Inovasi Nasional, 2025)
This Community Service activity focuses on strengthening mediation training for Damang and Mantir Adat in the Sebangau District, aiming to enhance their knowledge, skills, and professionalism in resolving community conflicts. The program was implemented by a team of lecturers from the Faculty of Law, Palangka Raya University, involving the Damang Customary Head, Mantir as Assistant Damang, the Sebangau District Head, and local village officials. This training was considered essential in accordance with Supreme Court Regulation (Perma) No. 1 of 2016 concerning Mediation Procedures in Court, particularly Article 36, which allows mediation outside the court to be facilitated by community or customary leaders. The main issue identified was the limited understanding among Damang and Mantir Adat regarding the proper format and procedures for drafting a legally binding Peace Agreement, as well as the follow-up mechanisms to ensure its enforcement under both Customary and National Law. Therefore, the training aimed to provide participants with the necessary legal knowledge and practical skills to prepare and implement peace agreements in compliance with existing regulations. During the sessions, participants actively engaged in discussions and question-and-answer activities. They were also introduced to a standardized peace agreement format and practiced drafting agreements using the provided template. This initiative successfully improved the capacity of Damang and Mantir Adat as mediators, enabling them to conduct conflict resolution processes that are both culturally rooted and legally valid.